Analisis Kualitas Nata De Corn Dari Ekstrak Jagung Kuning Muda Dengan Variasi Lama Fermentasi - sulistiyana, sulistiyana (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
In this research, nata de corn has been made from the young corn extract by Acetobacter xylinum. This research aims to make nata de corn with the variation of fermentation days and analyze the quality of nata de corn have been done. Fermentation days have been varied to look for the optimum conditions to obtain maximum quality. The variation of fermentation days was 11, 12, 13, and 14 days. Mass of young corn as substrate was 150 g/L solution. Then, Substrate was fermented using Acetobacter xylinum. The result of fermentation proses was called nata de corn. The nata de corn has been analyzed to obtain maximum % yield, water, and fibre content. The maximum % yield, water and fibre content were 46.82%, 93.13%, and 1.3%. This values in according to the standard quality of nata INS No.01-4317-1996.